Study of Participation from Related Sectors for Nam Po Demonsatration area Management of Vangvieng district, Vientiane Province, Lao PDR: https://doi.org/10.69692/SUJMRD100160 - Chanthavong, Souksakhone (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
The purpose of this research is: 1) To study the participation of related organizations in the management of Nam Po Demonstration Area, 2) To evaluate the activities of people's participation in the management of Nam Po Demonstration Area, 3) To promote activities that people benefit from and have income from various activities in the said area. The research method used in this study was to interview a sample group including: government officials from 6 offices, village level authorities in 7 villages and a sample group of people who represent all the people in 7 villages that are determined by using percentage criteria or estimation of values from the population which is considered to select 10% of the total population. Analysis of data from the interview with descriptive statistics using 02 programs: Excel and SPSS. The research results found: The participation of relevant parties in the management of Nam Po demonstration area which includes staff level employees from 6 offices who participated in 10 activities (tasks). Among them, there are 07 activities with an average value ( =3; meaning: regular participation) and another 03 activities with an average value ( =2; meaning: occasional participation) and people's participation in the management of the Nam Po demonstration area includes 4 activities such as participation in studying the problem situation and finding ways to solve the problem; Participating in awareness, dissemination of information and implementation of management tasks; Contributing labor and material to management work; Participating in planning, following the plan, monitoring, evaluating and reporting the results of the management of Nam Po demonstration area in 4 activities, it is seen that the level of participation is equal to the average value ( =3; means: moderate level participation). For the promotion of activities that people benefit from and have income from Nam Po Demonstration Area: promoting the development of tourist attractions, creating careers or hiring people in the area to work in the activities in the tourist attractions that have been created; Promote knowledge and train people who have the knowledge to assemble according to the needs of various activities created in the area; As well as promoting production in particular, agricultural production, creating activities and works that make the people in the area benefit the most directly or indirectly both now and in the future.